Patient-centered care coordination in hematopoietic cell transplantation - Nandita Khera; Patricia Martin; Kristen Edsall; Anthony Bonagura; Linda J. Burns; Mark Juckett; Olivia King; C. Frederick LeMaistre; Navneet S. Majhail (Blood Advances, 2017)
Abstract: Hematopoietic cell transplantation (HCT) is an expensive, resource-intensive, and medically complicated modality for treatment of many hematologic disorders. A well-defined care coordination model through the continuum can help improve health care delivery for this high-cost, high-risk medical technology. In addition to the patients and their families, key stakeholders include not only the transplantation physicians and care teams (including subspecialists), but also hematologists/oncologists in private and academic-affiliated practices. Initial diagnosis and care, education regarding treatment options including HCT, timely referral to the transplantation center, and management of relapse and late medical or psychosocial complications after HCT are areas where the referring hematologists/oncologists play a significant role. Payers and advocacy and community organizations are additional stakeholders in this complex care continuum. In this article, we describe a care coordination framework for patients treated with HCT within the context of coordination issues in care delivery and stakeholders involved. We outline the challenges in implementing such a model and describe a simplified approach at the level of the individual practice or center. This article also highlights ongoing efforts from physicians, medical directors, payer representatives, and patient advocates to help raise awareness of and develop access to adequate tools and resources for the oncology community to deliver well-coordinated care to patients treated with HCT. Lastly, we set the stage for policy changes around appropriate reimbursement to cover all aspects of care coordination and generate successful buy-in from all stakeholders.